2021
DOI: 10.3389/fncir.2021.644743
|View full text |Cite
|
Sign up to set email alerts
|

Adjudicating Between Local and Global Architectures of Predictive Processing in the Subcortical Auditory Pathway

Abstract: Predictive processing, a leading theoretical framework for sensory processing, suggests that the brain constantly generates predictions on the sensory world and that perception emerges from the comparison between these predictions and the actual sensory input. This requires two distinct neural elements: generative units, which encode the model of the sensory world; and prediction error units, which compare these predictions against the sensory input. Although predictive processing is generally portrayed as a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 165 publications
0
29
0
Order By: Relevance
“…This question has appeared in different forms, for example in early debates about whether sensory systems are modular (Fodor, 1985), or whether sensory input and contextual constraints are combined immediately in speech perception (Marslen- Wilson and Tyler, 1975;Tanenhaus et al, 1995). A similar distinction has also surfaced more recently between the local and global architectures of predictive coding (Tabas and von Kriegstein, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This question has appeared in different forms, for example in early debates about whether sensory systems are modular (Fodor, 1985), or whether sensory input and contextual constraints are combined immediately in speech perception (Marslen- Wilson and Tyler, 1975;Tanenhaus et al, 1995). A similar distinction has also surfaced more recently between the local and global architectures of predictive coding (Tabas and von Kriegstein, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Such a unified representation is consistent with empirical evidence for top-down modulation of sensory representations, for example, suggesting that recognizing a word can bias subsequent phonetic representations ( Luthra et al, 2021 ), that listeners weight cues like a Bayes-optimal observer during speech perception ( Bejjanki et al, 2011 ; Feldman et al, 2009 ), and that they immediately interpret incoming speech with regard to communicative goals ( Chambers et al, 2004 ; Heller et al, 2016 ). A recent implementation proposed for such a model is the global variant of hierarchical predictive coding, which assumes a cascade of generative models predicting sensory input from higher-level expectations ( Clark, 2013 ; Friston, 2010 ; Tabas and Kriegstein, 2021 ). A unified model is also assumed by classical interactive models of speech processing, which rely on cross-hierarchy interactions to generate a globally consistent interpretation of the input ( McClelland and Rumelhart, 1981 ; McClelland and Elman, 1986 ; Magnuson et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Such a unified representation is consistent with empirical results suggesting that word recognition can bias subsequent phonetic representations 28 , that listeners weight cues like a Bayes-optimal observer during speech perception 29,30 , and that they immediately interpret incoming speech with regard to communicative goals 31,32 . A recent implementation proposed for such a model is the global variant of hierarchical predictive coding, which assumes a cascade of generative models predicting sensory input from higher level expectations 25,33,34 . However, a unified model is also assumed by classical interactive models of speech processing, which rely on cross-hierarchy interactions to generate a globally consistent interpretation of the input [35][36][37] .…”
Section: Introductionmentioning
confidence: 99%
“…Formulations of the predictive coding framework disagree on whether predictions from generative model units inform prediction errors only at the immediate lower stage [10,79] or also at subsequent stages of the processing hierarchy (see [21] for a review of the empirical evidence on both standpoints). MMN studies showed that prediction error is elicited with respect to high-level expectations; namely: by the violation of complex statistical regularities (see [80] for review), the omission of expected sounds [81][82][83],…”
Section: Discussionmentioning
confidence: 99%
“…However, whether SSA truly represents prediction error is unclear: its phenomenology can be explained by habituation to local stimulus statistics [18][19][20] (see [21] for review, and [22] for a different perspective). One way to disambiguate habituation and prediction error is to manipulate participants' subjective stimulus expectations orthogonally to local stimulus statistics [21,23]. Prediction error to subjective expectations has been studied measuring the mismatch negativity (MMN) [24][25][26][27][28][29][30], partially generated in the frontal cortex [31,32].…”
Section: Introductionmentioning
confidence: 99%